Factors affecting sustained employment of people with chronic illness - Reynolds, Anne Patricia (My University, 2015)
Numerous factors influence the employment of people with chronic illness. At some point, these people withdraw from the labour market. This has both a direct and indirect cost to the person, their family and society as a whole. Aim: To explore the factors affecting sustained employment of people with chronic illness. A second component explored participants’ opinions regarding return to work in the future. Research Methods: The study was done in two phases: 1) The identification and validation of the research instrument; and 2) The administration of the research instrument. Descriptive statistics were utilised to analyse data obtained from the research instrument. Two sets of correlations were run to identify significant differences between the participants expecting to return to work and those who did not expect to return to work. Results: Descriptive statistics revealed no meaningful trend on self-reported factors. The Mann-Whitney U identified a number of significant differences between participants expecting to return to work and those who did not expect to return to work, in both personal and contextual factors. Conclusion: A broad range of factors were elicited regarding the barriers and accommodations required for sustained employment within both the personal and environmental constructs. Self-report questionnaires provided some useful information, but a broader understanding of the factors influencing work was obtained from a comprehensive interview. Significant differences were present between people expecting to return to work and those who did not expect to return to work regarding environmental and personal factors as well as factors supporting work.
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy Johannesburg, 2015
Keywords: Unemployment; Chronic Disease